2016
DOI: 10.15288/jsad.2016.77.349
|View full text |Cite
|
Sign up to set email alerts
|

Young Adults’ Exposure to Alcohol- and Marijuana-Related Content on Twitter

Abstract: ABSTRACT. Objective: Twitter is among the most popular social media platforms used by young adults, yet it has been underutilized in substance use research compared with older platforms (e.g., MySpace and Facebook). We took a first step toward studying the associations between exposure to pro-alcohol-and marijuana-related content among young adults via Twitter and current heavy episodic drinking and current marijuana use, respectively. Method: We conducted an online survey of 587 (254 men, 333 women) Twitter u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 28 publications
0
44
1
Order By: Relevance
“…There is recent evidence that the likelihood of participants' binge drinking substantially increased with exposure to pro-alcohol content in Tweets or on Facebook (CabreraNguyen, Cavazos-Rehg, Krauss, Bierut, & Moreno, 2016;D'Angelo, Kerr, & Moreno, 2014;Moreno, Cox, Young, & Haaland, 2015). The effects of social media on individual binge drinking were also found over time (D'Angelo et al, 2014).…”
Section: Social Factors (Iii): the Wider Social Environmentmentioning
confidence: 99%
“…There is recent evidence that the likelihood of participants' binge drinking substantially increased with exposure to pro-alcohol content in Tweets or on Facebook (CabreraNguyen, Cavazos-Rehg, Krauss, Bierut, & Moreno, 2016;D'Angelo, Kerr, & Moreno, 2014;Moreno, Cox, Young, & Haaland, 2015). The effects of social media on individual binge drinking were also found over time (D'Angelo et al, 2014).…”
Section: Social Factors (Iii): the Wider Social Environmentmentioning
confidence: 99%
“…The associations between health behaviors and social media use among youth and young adults have been studied in depth in myriad contexts, including behaviors such as alcohol consumption (Moreno & Whitehill, 2014), body image (Fardouly et al, 2015), and marijuana use (Cabrera-Nguyen et al, 2016). Further, portrayals of alcohol and other substances are prevalent on social media (Beullens & Schepers, 2013;Cabrera-Nguyen et al, 2016;Cranwell et al, 2017;Moreno et al, 2016), including posts related to marijuana (Cavazos-Rehg et al, 2015;Krauss et al, 2015;Thompson et al, 2015). Most social media posts about marijuana, across a variety of social media platforms, portray marijuana positively (Cavazos-Rehg et al, 2015.…”
Section: Social Mediamentioning
confidence: 99%
“…Cross-sectional surveys report that young adults are aware of, and have participated with, a range user-created alcohol promotion. For instance, 32% report that they have uploaded pictures of themselves consuming alcohol to social media (Morgan, Snelson, & Elison-Bowers, 2010), 56% report that they have uploaded pictures of their peers drinking (Glassman, 2012), 83% report that they are aware of pictures posted by others which document peer consumption (Morgan et al, 2010), 38% report that they have posted on Twitter about alcohol or followed an account which promotes drinking (Cabrera-Nguyen, Cavozos-Rehg, Krauss, Bierut, & Moreno, 2016), and 54% report that they took part in the Neknominate drinking game (Moss et al, 2015). Longitudinal surveys and experimental designs have further suggested that awareness of, and participation with, user-created alcohol promotion is associated with willingness to drink, frequency of consumption, and higher-risk drinking (Boyle, LaBrie, Froidevaux, & Witkovic, 2016;D'Angelo, Kerr, & Moreno, 2014;Litt & Stock, 2011;Marczinski et al, 2016;Pumper & Moreno, 2013).…”
Section: User-created Alcohol Promotion and Alcohol Consumption In Yomentioning
confidence: 99%